Role of methyleprednisolone succinate in the management of acute spinal cord injury (Health Renaissance, 2011)
Objective: To see the role of methyleprednisolone succinate in the management of acute spinal cord injury. Methods: A randomized control trial was done including the patients with acute spinal cord injury. They were divided into age and gender matched two groups. Patients with presence of active infection, associated open fracture, those on long term steroid and those who did not give consent to participate in the trial were excluded. One group received methyleprednisolone succinate within 8 hours of injury and another group did not receive the drug. Both the groups were managed nonoperatively. The neurological status of the patients was assessed at presentation, once spinal shock was over, at 6th week and 6th month and after one year according to ASIA scoring. Frankel grading was also assessed in every follow up. Conclusion: Methylprednisolone succinct prevents secondary cord injury to a great extent and hence its administration within 8 hours of injury results in a better functional (motor and sensory) outcome. Keywords: acute spinal cord injury; methyleprednisolone succinate DOI: http://dx.doi.org/10.3126/hren.v9i3.5585   HR 2011; 9(3): 168-172